Development of Heterogeneous Network and Wi-Fi Technology Will Effectively Address the Issue of Large Quantity of Data Service - Qian Xu; Gang Li (Dianxin kexue)
With the rapid development of mobile communication technology, it is believed that the 4th generation technology is approaching. The convergence of heterogeneous network becomes significant for network development, and it is also considered as the main feature of network structure. On the other side, Wi-Fi technology is also very important for heterogeneous network, it develops constantly recently. This article discusses how heterogeneous network and Wi-Fi technology improve the convergence of networks, and addresses the issue of large quantity of data service.